Anaerobic domestic wastewater treatment in a sequencing granular UASB bioreactor: Feasibility study of the temperature effect on the process performance. Issue 5 (October 2022) - Stazi, Valentina; Annesini, Maria Cristina; Tomei, Maria Concetta
Abstract: A laboratory-scale sequencing granular up-flow anaerobic sludge blanket (UASB) reactor was applied for the treatment of synthetic domestic wastewater at 15, 25 and 35 °C. The experiments were performed at different hydraulic retention times (gradually decreasing from a maximum of 22 h to a minimum of 9 h). Results at 25 and 35 °C showed similar COD removal efficiency and specific biogas production in the range of 84–94% and 0.14–0.27 m 3 /kgCODremoved, respectively. At 15 °C lower COD removal kinetics were observed, and a minimum hydraulic retention time of 14 h was necessary to obtain an effluent in accordance with current Italian legislation. At all temperatures, high quality effluent was achieved in terms of total suspended solids (TSS) concentration, while nitrogen and phosphorus exceeded the Italian law limits, as they are not removed during the anaerobic digestion process. Moreover, dissolved methane in the liquid phase was analysed: methane lost with the effluents was on average ≈ 37% at 25 °C and ≈ 24% at 35 °C of the produced amount, thus revealing higher losses at lower temperatures for the increase of gas solubility. These results show the need of research on technologies aimed at removing or recovering such energetic greenhouse gas. However, effective biogas production and potentialities for nutrients' recovery demonstrated in this study confirm the feasibility of the anaerobic process as sustainable treatment of low-strength wastewaters. Graphical Abstract: ga1 Highlights: Verified feasibility of a sequential granular UASB for domestic wastewater treatment. Successful treatment of domestic wastewater at 35 and 25 °C for all tested HRTs. Satisfactory biogas production at different temperatures and tested HRTs. Analysis of dissolved CH4 in treated effluent and strategies for its recovery/reuse. Concentrations of nutrient in the treated effluent suitable for agricultural reuse.